Multilingual Youth and Identity Negotiation in Ambon’s Urban–Traditional Community: A Sociolinguistic Ethnography - Manuputty, Feky; Makaruku, Nathalia Debby (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2023)
This study explores how young people in Hukurila, a customary village within the administrative area of Ambon City, use language to negotiate social identities amid the tension between traditional values and urban modernity. While Hukurila maintains customary institutions such as the mata rumah parentah system, ritual practices, and local language, its youth’s interaction with urban schools, digital media, and popular culture has fostered hybrid linguistic practices blending urban Indonesian, Ambon Malay, English, and digital symbols. Employing a sociolinguistic ethnography within an interpretive–critical paradigm, data were collected through participant observation, sociolinguistic interviews, recorded conversations, and online ethnography involving youth aged 13–20 across home, school, church, community, and social media contexts. Findings reveal the emergence of hybrid linguistic identities, where Ambon Malay indexes local solidarity, while urban Indonesian and English-mixed slang signify modernity and social mobility. The local Hukurila language is rarely used in daily interactions but retains symbolic value in customary and religious domains. Language ideologies have shifted, language now serves as a marker of coolness, social belonging, and global aspiration. The study introduces the concept of Urban–Adat Multilingualism, describing communities that sustain traditional linguistic systems within urban social environments. It advances sociolinguistic scholarship by linking offline and online ethnography to examine youth language as social and ideological practice, highlighting the need for inclusive language education and context-sensitive approaches to multilingual identity in Eastern Indonesia.